A DNA Vaccine Encoding SA-4-1BBL Fused to HPV-16 E7 Antigen Has Prophylactic and Therapeutic Efficacy in a Cervical Cancer Mouse Model - Garza Morales, Rodolfo; Pérez Trujillo, José Juan; Martínez Jaramillo, Elvis; Saucedo Cárdenas, Odila; Loera Arias, María de Jesús; García García, Aracely; Rodríguez Rocha, Humberto; Yolcu, Esma; Shirwan, Haval; Gomez Gutierrez, Jorge G; Montes de Oca Luna, Roberto (2019)
TheSA-4-1BBL,anoligomericnovelformofthenaturalligandforthe4-1BBco-stimulatory receptorofthetumornecrosisfactor(TNF)superfamily,asarecombinantproteinhaspotentpleiotropic eﬀects on cells of innate, adaptive, and regulatory immunity with demonstrated therapeutic eﬃcacy in several tumor models. However, the production of soluble form of SA-4-1BBL protein and quality control is time and resource intensive and face various issues pertinent to clinical development of biologics. The present study sought to take advantage of the simplicity and translatability of DNA-based vaccines for the production and delivery of SA-4-1BBL for cancer immune prevention and therapy. A chimeric HPV-16 E7 DNA vaccine (SP-SA-E7-4-1BBL) was constructed that contains the signal peptide (SP) of calreticulin (CRT), streptavidin (SA) domain of SA-4-1BBL, HPV-16 E7 double mutant gene, and the extracellular domain of mouse 4-1BBL. Immunization by gene gun with SP-SA-E7-4-1BBL induced greater prophylactic as well as therapeutic eﬀects in C57BL/6 mice against TC-1 tumor model compared with immunization with E7wt, SP-SA-4-1BBL or reference-positive control CRT-E7wt. The therapeutic eﬃcacy of the DNA vaccine was associated with increased frequency of E7-speciﬁc T cells producing interferon (IFN)-γ. Overall, our data suggest that this DNA-based vaccine strategy might represent a translational approach because it provides a simpler and versatile alternative to a subunit vaccine based on SA-4-1BBL and E7 proteins.